Karakteristik Fisikokimia dan Sensori Fruit Leather dari Campuran Buah Sirsak dan Buah Nangka - Handarbeni, Rifqi Gusti; Rahmayuni, Rahmayuni; Rossi, Evy (Agriculture Faculty, 2024)
Fruit leather is a processed food derived from dried pulp, so it is a thin sheet that can be rolled up and has a distinctive flavor depending on the fruit as the raw material. This study aimed to obtain the best ratio of soursop and jackfruit on fruit leather's physicochemical and sensory characteristics. The fruit leather treatment in this study was the ratio of soursop pulp and jackfruit pulp, namely SN (80:20), SN (70:30), SN (60:40), and SN (50:50). The data obtained were statistically analyzed using ANOVA test. If the calculated F value is greater than or equal to the F table, proceed with Duncan's Multiple Range Test (DMRT) at the 5% level. The results of variance analysis showed that the ratio of soursop pulp and jackfruit pulp had a significant effect on moisture content, ash content, acidity (pH), fiber content, total sugar content, color test, and sensory assessment consisting of descriptive test and hedonic test. This study's selected fruit leather treatment was SN treatment of soursop pulp and jackfruit pulp (70:30). 11,47% moisture content, 0,49% ash content, 3,68 pH value, 0,38% crude fiber content, 51,73% total sugar content, color test L* value 58,68, a* value 10,94, and b* value 22,94. The descriptive test obtained yellow color, a slight jackfruit scent, a slight jackfruit taste, and a chewy texture. Assessment of color, taste, chewiness, and overall assessment was liked, and the panelists slightly liked the scent.